Nitrogen and phosphorus uptake by maize as affected by particulate organic matter quality, soil characteristics, and landuse history for soils from the West African moist savanna zone - Vanlauwe, Bernard; Aihou, K.; Tossah, S.; Aman, B.K.; Diels, J.; Lyasse, O.; Hauser, S.; Sanginga, P.; Merckx, Roel (Springer, 2000)
The impact of land use (unfertilized continuous maize cropping, unfertilized and fertilized alley cropping with maize, Gliricidia sepium tree fallow, natural fallow) on the soil organic matter (SOM) status and general soil fertility characteristics were investigated for a series of soils representative for the West African moist savanna zone. Three soils from the humid forest zone were also included. In an associated pot experiment, relationships between maize N and P uptake and SOM and general soil characteristics were developed. Soils under natural fallow contained the highest amount of organic C (1.72%), total N (0.158%), and had the highest effective cation exchange capacity (ECEC) [8.9 mEq 100 g–1 dry soil], while the Olsen P content was highest in the fertilized alley cropping plots (13.7 mg kg–1) and lowest under natural fallow (6.3 mg kg–1). The N concentration of the particulate organic matter (POM) was highest in the unfertilized alley cropping plots (2.4%), while the total POM N content was highest under natural fallow (370 mg N kg–1) and lowest in continuously cropped plots (107 mg N kg–1). After addition of all nutrients except N, a highly significant linear relationship (R2=0.91) was observed between the total N uptake in the shoots and roots of 7-week-old maize and the POM N content for the savanna soils. POM in the humid forest soils was presumably protected from decomposition due to its higher silt and clay content. After addition of all nutrients except P, the total maize P uptake was linearly related to the Olsen P content. R2 increased from 0.56 to 0.67 in a multiple linear regression analysis including the Olsen P content and clay content (which explained 11% of the variation in P uptake). Both the SOM status and N availability were shown to be improved in land-use systems with organic matter additions, while only the addition of P fertilizer could improve P availability.